Assessment of Growth and Biomass Production of a Medicinal Plant Bryophyllum Salisb. as Influenced by Different Organic Manures - Sharif, AT; Razzaque, AS; Purna, TT; Rahman, Md Khalilur (Dhaka University Journal of Biological Sciences, 2020)
A pot experiment was carried out to evaluate the influence of various organic manures on the growth performance and biomass production of Bryophyllum pinnatum. Nine kinds of organic manures, such as ACI, BGF-1, bone meal, Green life, Kazi, Majim, mustard cake, Payel and Shebok composts were applied individually at the rate of 15 ton/ha. Highest height (45.25 cm), leaf number (102.67 no./plant), leaf area (82.43 cm2/plant), number of branches (27.00 no./plant), girth (6.75 cm/plant), total fresh weight (334.02 g/plant) and total dry weight (86.09 g/plant) were recorded in mustard cake compost treatment at harvest. Results showed that the best growth performance and biomass production both were achieved by mustard cake compost treatment. Dhaka Univ. J. Biol. Sci. 29(2): 229-236, 2020 (July)